Cancers related to lifestyle and environmental factors in France in 2015. (December 2018) - Soerjomataram, Isabelle; Shield, Kevin; Marant-Micallef, Claire; Vignat, Jerome; Hill, Catherine; Rogel, Agnes; Menvielle, Gwenn; Dossus, Laure; Ormsby, Jean-Nicolas; Rehm, Jurgen; Rushton, Lesley; Vineis, Paolo; et al.
Abstract: Background: Cancer is a major cause of premature illness and death in France. To quantify how cancer prevention could reduce the burden, we present estimates of the contribution of lifestyle and environmental risk factors to cancer incidence in France in 2015, comparing these with other high-income countries. Method: Prevalences of, and relative risks for tobacco smoking, alcohol consumption, inadequate diet, overweight and obesity, physical inactivity, exogenous hormones, suboptimal breastfeeding, infectious agents, ionising radiation, air pollution, ultraviolet exposure, occupational exposures, arsenic in drinking water and indoor benzene were obtained to estimate the population attributable fraction (PAF) and the number of attributable cancers by the cancer site and sex. Results: In 2015, 41% (or 142, 000 of 346, 000) of all new cancers diagnosed in France could be attributed to the aforementioned risk factors. The numbers and PAF were slightly higher in men than in women (84, 000 versus 58, 000 cases and 44% versus 37%, respectively). Smoking (PAF: 20%), alcohol consumption (PAF: 8%), dietary factors (PAF: 5%) and excess weight (PAF: 5%) were the most important factors. Infections and occupational exposures each contributed to an additional 4% of the cancer cases in 2015. Conclusion: Today, two-fifths of cancers in France are attributable to preventable risk factors. The variations in the key amenable factors responsible in France relative to other economically similar countries highlight the need for tailored approaches to cancer education and prevention. Reducing smoking and alcohol consumption and the adoption of healthier diet and body weight remain important targets to reduce the increasing number of new cancer patients in France in the decades to follow. Highlights: 41% of all new cancers diagnosed in France could have been avoided. The proportion of avoidable cancer is similar to that in other countries, but variations were seen in the ranking of major risk factors. In France, smoking, alcohol consumption, unhealthy diet and excess weight were the most important cancer risk factors. Long latency time of prevention programme warrants prompt action to ensure future reduction in cancer burden.